Antitumour activity of pembrolizumab in advanced mucosal melanoma: a post-hoc analysis of KEYNOTE-001, 002, 006. Issue 6 (11th September 2018) - Hamid, Omid; Robert, Caroline; Ribas, Antoni; Hodi, F.; Walpole, Euan; Daud, Adil; Arance, Ana; Brown, Ewan; Hoeller, Christoph; Mortier, Laurent; Schachter, Jacob; Long, Jianmin; et al.
Abstract Background Mucosal melanoma is an aggressive melanoma with poor prognosis. We assessed efficacy of pembrolizumab in patients with advanced mucosal melanoma in KEYNOTE-001 (NCT01295827), −002 (NCT01704287), and −006 (NCT01866319). Methods Patients received pembrolizumab 2 mg/kg every 3 weeks (Q3W) or 10 mg/kg Q2W or Q3W. Response was assessed by independent central review per RECIST v1.1. Results 1567 patients were treated and 84 (5%) had mucosal melanoma. Fifty-one of 84 were ipilimumab-naive. In patients with mucosal melanoma, the objective response rate (ORR) was 19% (95% CI 11–29%), with median duration of response (DOR) of 27.6 months (range 1.1 + to 27.6). Median progression-free survival (PFS) was 2.8 months (95% CI 2.7–2.8), with median overall survival (OS) of 11.3 months (7.7–16.6). ORR was 22% (95% CI 11–35%) and 15% (95% CI 5–32%) in ipilimumab-naive and ipilimumab-treated patients. Conclusion Pembrolizumab provides durable antitumour activity in patients with advanced mucosal melanoma regardless of prior ipilimumab.